Real-Time Monitoring of Cancer Cells in Live Mouse Bone Marrow - Lee, Sung Hwan; Park, Sang A; Zou, Yunyun; Seo, Sang-Uk; Jun, Chang-Duk; Lee, Woo Jung; Hyun, Young-Min; Cho, Nam Hoon (Frontiers in Immunology, 2018)
Disseminated tumor cells in the bone marrow environment are the main cause of systemic metastasis after curative treatment for major solid tumors. However, the detailed biological processes of tumor biology in bone marrow have not been well defined in a real-time manner, because of a lack of a proper in vivo experimental model thereof. In this study, we established intravital imaging models of the bone marrow environment to enable real-time observation of cancer cells in the bone marrow. Using these novel imaging models of intact bone marrow and transplanted bone marrow of mice, respectively, via two-photon microscopy, we could first successfully track and analyze both the distribution and the phenotype of cancer cells in bone marrow of live mouse. Therefore, these novel in vivo imaging models for the bone marrow would provide a valuable tool to identify the biologic processes of cancer cells in a real-time manner in a live animal model.